1994
DOI: 10.1002/bit.260431122
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric analysis of animal cell growth and its application in medium design

Abstract: Animal cell cultivation in vitro has been studied for more than 40 years. However, the culture medium composition has not been designed on the basis of the stoichiometric nutritional demands for animal cell growth. In this article, a model was developed to study the stoichiometric demands for nutrients (including glucose, 20 amino acids, and 10 vitamins)for the synthesis of cell mass and product. The coefficients for these nutrients in the stoichiometric equation governing animal cell growth were determined ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 26 publications
1
83
0
Order By: Relevance
“…Earlier reports of Zhu et al [23] using stoichiometric analysis optimization method developed by Xie and Wang [24] had indicated that certain amino acids were required for enhanced production of transglutaminase enzyme. As it would not be possible to add these amino acids in pure form in a practical system, ®nding a supplementary nitrogen source rich in amino acids composition will be more economic.…”
Section: Effect Of Nitrogen Source and Concentrationmentioning
confidence: 99%
“…Earlier reports of Zhu et al [23] using stoichiometric analysis optimization method developed by Xie and Wang [24] had indicated that certain amino acids were required for enhanced production of transglutaminase enzyme. As it would not be possible to add these amino acids in pure form in a practical system, ®nding a supplementary nitrogen source rich in amino acids composition will be more economic.…”
Section: Effect Of Nitrogen Source and Concentrationmentioning
confidence: 99%
“…In the second phase, from 40 to 75 h, the specific heat flow rate showed a continuous decline coincident with the fact that the concentrations of glucose and glutamine in the medium decreased to such an extent that the amounts of them were minimal at 75 h. When considering this, it is important to know that the K m for glutamine in cell growth is between 0.09 and 0.53 mM, depending on cell type (Jeong and Wang, 1995;Xie and Wang, 1994) and that of glucose, 0.5 to 1.5 mM (Xie and Wang, 1994). For Monod-type substrate effects, this implies that for at least the majority of the growth phase of the CHO 320 cells, changes in the reaction stoichiometry were due to alterations in cellular metabolism rather than to the kinetics of substrate uptake.…”
Section: Specific Heat Flow Rate and The Changing Growth Reaction Stomentioning
confidence: 99%
“…To meet the requirement of essential nutrients for growth and to prevent their depletion, the stoichiometric demands of glucose, amino acids, and vitamins were studied (Xie and Wang, 1994b). Reduction of ammonia and lactate formation was achieved by feeding the supplemental medium according to the needs for cell growth and product formation (Xie and Wang, 1994a,c).…”
Section: Introductionmentioning
confidence: 99%